Pengaruh Perhatian Orang Tua Dan Kendali Diri Terhadap Hasil Belajar Siswa Pada Mata Pelajaran Aqidah Akhlaq Di Mts. Daruttaqwa I Watukosek Gempol Pasuruan - Ilusia Insyirah; Didit Darmawan (Journal on Education, 2025)
Learning outcomes are an indicator of the success of a learning process and are a measure used to assess whether students have achieved a set level of competence. The importance of understanding the effects of parental attention and self-control on students' learning ability in Aqidah Akhlaq learning is not only to achieve academic achievement, but also to develop a strong personality and morals. The purpose of this study was to determine how parental attention and self-control affect student learning outcomes in the subject of Aqidah Akhlaq at MTs. Darut Taqwa I watukosek Gempol pasuruan. This study applies quantitative methodology with a population of 47 students, determining the sample using purposive total sampling technique so that the sample in this study was 47 students. The method applied to evaluate the effect of these variables on student learning outcomes is multiple linear regression analysis. The results show that parental attention and self-control have a good and significant effect on student learning outcomes. The results of this study confirm the importance of parental attention in improving student learning outcomes optimally, therefore parental attention can help improve student academic achievement as well as the quality of education in the subject of akhlaq. Self-control has an important role in time management and effective learning techniques to help them optimise their learning.